Pengembangan eLEMA 2.0 untuk Mata Kuliah Zoologi Invertebrata pada Topik Filum Arthropoda - Adam, Chaidir; Haryono, Agus; Araina, Elga; Savitri, Shanty (Universitas Negeri Jakarta, 2024)
Currently, technology has become an inseparable part of education and learning. Various digital learning tools have been developed and widely used in the classroom. eLEMA (electronic learning materials) was developed as a mobile application that supports learning in the Invertebrate Zoology courses at the Biology Education Program, University of Palangka Raya. At that time, eLEMA was developed to meet the need for electronic learning materials for online learning during the COVID-19 pandemic. Along with the rapid development of technology in recent years, eLEMA needs to be developed further for updates. This research aims to develop eLEMA 2.0 for the Invertebrate Zoology course. This study is a research and development (R & D) using Hannafin & Peck development model to develop eLEMA 2.0 for the Invertebrate Zoology course on the Phylum Arthropoda topic. The development product is the eLEMA 2.0 application for lectures on the Phylum Arthropoda topic in the Invertebrate Zoology course with improvements to the user interface and additional features that support participatory learning and student-centered learning. The results of trials and validation show that all pages and content in this application were successfully opened without any disturbing errors. These results indicate that the development product is feasible to be implemented in the classroom.